2014
DOI: 10.7554/elife.03523
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as a source of new peptides

Abstract: Deep transcriptome sequencing has revealed the existence of many transcripts that lack long or conserved open reading frames (ORFs) and which have been termed long non-coding RNAs (lncRNAs). The vast majority of lncRNAs are lineage-specific and do not yet have a known function. In this study, we test the hypothesis that they may act as a repository for the synthesis of new peptides. We find that a large fraction of the lncRNAs expressed in cells from six different species is associated with ribosomes. The patt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
420
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(439 citation statements)
references
References 101 publications
13
420
0
6
Order By: Relevance
“…Interestingly these smORFs have Ribo-seq ORFscore values that are higher than non-coding controls, but lower than annotated smORFs. Similarly, Ruiz-Orera et al [76] found that, in several species, smORFs in lncRNAs have intermediate Ribo-seq and conservation features, which resemble those of newly evolved peptides. These results are, overall, reminiscent to those of Aspden et al [32] in Drosophila, reinforcing the idea of functionally distinct classes of smORFs.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 86%
“…Interestingly these smORFs have Ribo-seq ORFscore values that are higher than non-coding controls, but lower than annotated smORFs. Similarly, Ruiz-Orera et al [76] found that, in several species, smORFs in lncRNAs have intermediate Ribo-seq and conservation features, which resemble those of newly evolved peptides. These results are, overall, reminiscent to those of Aspden et al [32] in Drosophila, reinforcing the idea of functionally distinct classes of smORFs.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 86%
“…When combined with RNA-seq generated from the same starting material, one can accurately determine the average number of ribosomes per mRNA and thus estimate the relative translation levels of a transcript (2). Furthermore, localization of the exact positions of ribosome footprints in the transcriptome provides the opportunity to experimentally identify translated ORFs genome-wide under a specific environment (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…13 The generally accepted definition of a lncRNA is a transcript that lacks a long or conserved open reading frame and is greater than 200 nucleotides in length. 1,14 Initially theorized to be the result of spontaneous, aberrant transcription initiation, lncRNAs were first dismissed as spurious "sloppy" transcription. 15 However, the characterization of gene regulatory functions by mammalian lncRNAs, such as XIST 16 and HOTAIR, 17 made it clear that many of these transcripts are much more than extraneous transcriptional products.…”
mentioning
confidence: 99%